Legal Protection for Traditional Knowledge of the Sumenep Keris - Djulaeka, Djulaeka; Suharyanto, Moh. Nofry; Zulkifli, Makhmud; Farizi, Salfanil (Faculty of Law Universitas Trunojoyo Madura, 2024)
This research was conducted to conduct a study on keris as a souvenir in Sumenep Regency. The nickname of the city of Keris for Sumenep provides an attraction to conduct a study related to efforts to provide protection for Sumenep keris as part of traditional knowledge because of the way of making and characteristics of Sumenep keris that are different from other regions in Indonesia. This research contributes to the effort to provide a theoretical study of keris in Sumenep as part of communal intellectual property. Traditional knowledge as part of communal intellectual property needs to be recorded as a defensive protection, so this research needs to be carried out. Through a factual and legal approach, the Sumenep keris can meet the requirements as part of the Communal Intellectual Property (Communal IP) so that political will is a signal of efforts to be able to provide preservation, including the protection of the Sumenep keris as traditional knowledge that must be maintained in a descending manner by the community and the local government.